Running Boot Camp - Toporek, Chuck, 1965- (O'Reilly, 2006)
When Steve Jobs jumped on stage at Macworld San Francisco 2006 and announced the new Intel-based Macs, the question wasn't if, but when someone would figure out a hack to get Windows XP running on these new "Mactels." Enter Boot Camp, a new system utility that helps you partition and install Windows XP on your Intel Mac. Boot Camp does all the heavy lifting for you. You won't need to open the Terminal and hack on system files or wave a chicken bone over your iMac to get XP running. This free program makes it easy for anyone to turn their Mac into a dual-boot Windows/OS X machine. Running Boot Camp guides you step-by-step through the entire installation process, including upgrading your Mac's Firmware, creating the Macintosh Drivers CD to make XP work properly with your Mac's hardware, and using the Boot Camp Assistant to partition your hard drive and install Windows XP. You'll also learn how to avoid common pitfalls (such as previously partitioned drives and wrong disk permissions). And finally, you'll find out which Mac functions don't work in XP and which XP features backfire on a Mac. With this invaluable guide at your side, you'll finish configuring your dual-boot Mac in as little as two hours, avoiding numerous hazards and annoyances along the way